Endocrine profile dataset of fasting and normally eating young, healthy men and following activation of brain areas involved in ingestive behaviour - Janis M. Nolde; Sophia G. Connor; Arkan Al-Zubaidi; Jana Laupenmühlen; Marcus Heldmann; Kamila Jauch-Chara; Thomas F. Münte (Data in Brief, 2019)
Data includes endocrine data (adiponectin, ACTH, cortisol, C-peptide, insulin and glucose) of a 38 hour fasting intervention and a control condition with standardised meals in young healthy male subjects. The data was collected using a within-design approach. The data of ten common bilateral regions of interest (ROIs) involved in ingestive behaviour are included as fMRI percent signal change measurements of the amygdala, caudate nucleus, insula (classified into three regions), nucleus accumbens (NAcc), orbitofrontal cortex (OFC, classified into two different regions), pallidum, and lastly, the putamen. These measurements were performed whilst images of food were shown to participants during fMRI who would rate them on a scale from 1 to 8. Reaction times as well as each image's score are also included in the dataset. Endocrine data is especially useful as it is a well-controlled dataset of healthy young males in fasting and satiated conditions. Furthermore, this data can provide a physiological reference for experiments in patients with impaired glucose tolerance or metabolic syndrome. fMRI data may be useful as an extension of an existing dataset or for replication of the collected data. Keywords: Fasting, Endocrine, Adiponectin, Glucose metabolism, fMRI